Therapy correction of concerned chronic heart failure and chronic obstructive pulmonary disease in a patient with first identified pulmonary tuberculosis. Case report - Natalia V. Bagisheva; Anna V. Mordyk; Dmitry I. Trukhan; Inna A. Viktorova; Marina V. Moiseeva (ZAO "Consilium Medicum", 2022)
Chronic heart failure and chronic obstructive pulmonary disease in some cases are comorbid conditions characterized by a more severe course of each of the diseases and worsening the prognosis for the patient. Additional efforts from the doctor are required when pulmonary tuberculosis is added in this category of patients to improve treatment outcomes. A clinical example of the correction of therapy for chronic heart failure and chronic obstructive pulmonary disease in a patient with pulmonary tuberculosis is given.